Nurse-community health mediator pairs: a promising model for promoting the health of populations in remote areas of the French Amazon - Gaillet, Mélanie; Oberlis, Margot; Bonot, Bérengère; Cochet, Charlène; Jacoud, Estelle; Michaud, Céline; Amato, Lionel; Rousseau, Cyril; Caspar, Cécile; Boussat, Bastien; Vignier, Nicolas; Epelboin, Loïc; et al. (Frontiers in Public Health, 2025)
Multicultural Amazonian populations in remote areas of French Guiana face challenges in accessing healthcare and preventive measures. They are geographically and administratively isolated. Health mediation serves as an interface between vulnerable people and the professionals involved in their care. This approach aims to improve the health of Amazonian populations by addressing their unique challenges, including social and health vulnerabilities, as well as language and cultural barriers. A Mobile Public Health Team (MPHT) relying on health mediation was created in 2019. Comprising six nurse–community-health mediator pairs who receive ongoing specialised training, along with a coordination team of one physician and two public health nurses, the MPHT is connected to the 17 Prevention and Care Remote Centres across the territory. This article presents a community case study of the MPHT of the remote areas in French Guiana and the description of the activities of this health promotion programme in the context of the COVID-19 pandemic in 2021. The MPHT carried out health promotion initiatives, often in collaboration with partners, focusing on health priorities of the Amazonian territories. The interventions were co-designed with community leaders and local populations to ensure relevance and effectiveness. In response to the COVID-19 pandemic, the MPHT reached over 6,000 individuals in addition to more than 3,000 participants in a water, hygiene and sanitation education programme. The team performed 83 health promotion interventions on eight different topics, including 28 in the general population (922 people reached) and 55 in schools (n = 930). The MPHT produced 20 communication tools, which were adapted and translated into eight languages. The team also participated in managing six simultaneous epidemic events, including malaria, diphtheria, and tuberculosis. This study highlights how the combined expertise of healthcare professionals and the mediation skills of community health workers effectively addressed the specific health needs of the multicultural Amazonian populations. This model for addressing social and health inequities should encourage institutional recognition of the community health mediator model.